DETERMINAN MANAJEMEN LABA, STUDI META ANALISIS - Wibowo, Yohannes -; Jeconiah, Grayvien -; Tanthianto, Dion -; Meiden, Carmel - (Makro Jurnal Manajemen Dan Kewirausahaan, 2023)
Earnings management practices are expected to be minimized with strict supervision. This is due to the fact that one of the important measuring tools for decision making is profit information in financial statements. This study uses a meta-analysis method for testing. The population of this study is a journal found through Publish or Pearish 8 with the topic of factors that affect earnings management which includes deferred tax expense variables, deferred assets, tax planning, tax size and leverage for the 2010-2020 research year. In this study, purposive sampling method was used as a sampling strategy, using 31 articles as sample. The results of t-test statistics from journals used as secondary data, taken from several journals in Publish or Pearish 8. To combine the research findings of journals and ensure deferred tax expense, deferred tax assets, tax planning, size and influence have an influence on earnings management. The independent variable relationship with the variable is weak, with an average correlation value of less than 0.25. This study concludes that financial management is influenced by firm size, leverage, deferred assets, tax planning and deferred tax expense.